МЕЗОФАЗО- ТА СКЛОУТВОРЕННЯ В БІНАРНИХ СИСТЕМАХ АЛКАНОАТІВ ЦЕЗІЮ ТА БАРІЮ - Mirnaya, Tatiana; Yaremchuk, Galina; Bylina , Denis (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2021)
Phase equilibria in binary systems of individually non-mesomorphic components: propionates, isobutyrates, butyrates and valerates of cesium and barium at temperatures from 20 to 400 °C have been investigated by the methods of differential thermal analysis and polarization polythermal microscopy. In all systems, the formation of intermediate liquid-crystalline solutions of smectic modification (type A) was established. The temperature-concentration regions of the formation of ionic liquid crystals and glasses are determined. The studies carried out show that in binary systems of cesium and barium alkanoates intermediate liquid-crystal solutions are generated due to the latent mesomorphism of the corresponding cesium alkanoate and due to the eutectic decrease in liquidus temperatures in the binary systems. The thermal stability of the induced mesophase in the case of systems of the considered type is influenced by the following factors: the degree of ordering of the melt, which correlates with the length of the alkyl chain of the alkanoate anion, and a decrease in the temperatures of the liquidus line relative to the latent clearing temperature. The possible influence of compounds melting congruently or incongruently, formed in binary systems, should also be taken into account. Experimental data indicate the largest temperature-concentration range of the mesophase in the butyrate system, where there are the most favorable conditions for the implementation of intermediate liquid crystal solutions. Such conditions are the largest decrease in liquidus temperatures in a series of systems relative to the latent clearing point, as well as an additional increase in thermal stability due to the formation of a congruently melting compound of anisometric structure. In the case of the valerate system, a certain increase in anisotropy in comparison with the butyrate system is leveled by high liquidus temperatures; here is the narrowest region of existence of the intermediate mesophase due to its thermal destabilization.